Clinical characteristics and molecular genetic analysis of a cohort with idiopathic congenital hypogonadism - (:unkn) unknown (De Gruyter Open Ltd, 2021)
Objectives: Hypogonadism is defined as inadequate sex hormone production due to defects in the hypothalamic-pituitary-gonadal axis. In recent years, rare single gene defects have been identified in both hypergonadotropic hypogonadism (Hh), and hypogonadotropic hypogonadism (HH) cases with no chromosomal anomalies. The aim of the present study is to investigate the underlying molecular genetic etiology and the genotype-phenotype relationship of a series of patients with Hh and HH. Methods: In total, 27 HH and six Hh cases were evaluated. Clinical and laboratory features are extracted from patients’ hospital files. Whole exome sequencing (WES) analysis was performed. Results: A total of 27 HH cases (15 female) (mean age: 15.8 ± 2.7 years) and six Hh patients (six females) (mean age: 14.9 ± 1.2 years) were included. In molecular genetic analysis, a pathogenic/likely pathogenic variant was identified in five (two patients from the same family) of 27 HH cases (two novel) and three of the six Hh. In HH group variants (pathogenic, likely pathogenic and variant of uncertain significance) were identified in KISS1R (n=2), PROK2 (n=1), FGFR1 (n=1), HS6ST1 (n=1), GNRH1 (n=1) genes. In the Hh group, splice-site mutations were detected in DCAF17 (n=1) and MCM9 (n=2) genes. Conclusions: HH and Hh cases are genetically heterogeneous diseases due to oligogenic inheritance, incomplete penetrance, and variable expressivity. We found rare variants in CHH related genes in half of our HH cases, whereas they classified as pathogenic/likely pathogenic according to ACMG criteria in only about 15% of HH cases. Using advanced genetic analysis methods such as whole-genome sequencing and long-read sequencing may increase the mutation detection rate, which should always be associated with and expert genetic counseling to interpret the data. © 2021 De Gruyter. All rights reserved.
Keywords: Hypergonadotropic hypogonadism; Hypogonadotropic hypogonadism; Novel variant; Whole-exome sequencing